Distribución, abundancia y diversidad de los nematodos (phylum Nematoda) bénticos de la Sonda de Campeche, México. Enero 1987 - De Jesús-Navarrete, Alberto (Revista de Biología Tropical, 1993)
The distribution, abundance and diversity of benthic nematodes were studied at the Campeche Sound in me GuH of Mexico. Ten stations were sampled in January (1987). The marine sediments were collected with a Van Veen grab oC 0.1 m’. The community was represented by four orden, 39 families, 86 genera and 96 species. Tbe most frequent orden were: Chmnadorida, Monhysterida and Enoplida. In muddy-clay stations, the genera Dorylaimopsis,MetacoTMsomo and Sabatieria were dominant, whereas in sandy stations the genera Elzafia and Retrotheristus were the most abundanL Diversity (H’) was 4.0 bits/ind; minimum, and 5.87 bits/ind; maximum. Four feeding types: selective deposit fceders (lA), non-selective deposit fceden (lB), epistrate fceders (2A) and omnivores/predators (2B) were present in all statíons, hut types lA and lB were dominant particulary in muddy-clay sedúnents.